Value Based Thematics Learning - Tahmid Sabri (JETL (Journal of Education, Teaching and Learning), 2017)
Today, the ever-changing curriculum development in accordance with the power holder and the authority in issuing the policy has revamped the previous curriculum (Curriculum Unit of Education Unit) into the Curriculum 2013. This, of course, has an enormous impact on the implementation of life values in every aspect.